Morphologic Features Suggestive of Endometriosis in Nondiagnostic Peritoneal Biopsies. (November 2015) - Harrison, Beth T.; Mittal, Khush
Abstract : Endometriosis is a common disorder that causes significant morbidity from dysmenorrhea, pelvic pain, and subfertility. Establishment of a definitive diagnosis has important therapeutic implications; however, only approximately 50% of biopsies of laparoscopically suspicious areas provide a diagnosis of endometriosis. Histologic criteria for diagnosis require the presence of endometrial glands or endometrial-type stroma. We hypothesize that other frequently present, but nondiagnostic, histologic features of endometriosis suggest its presence in patients with nondiagnostic peritoneal biopsies. We performed a retrospective clinicopathologic study of morphologic and immunohistochemical features that may improve the histologic diagnosis of endometriosis on laparoscopic peritoneal biopsies. We compared diagnostic (n=88) and nondiagnostic (n=54) peritoneal biopsies from pathologically confirmed endometriosis cases with negative peritoneal biopsies (n=84) from early-stage gynecologic cancer cases. Statistical analysis utilized the Fisher exact test. Multiple morphologic features were significantly increased in nondiagnostic biopsies from patients with endometriosis in comparison with those from negative controls, including foamy macrophages ( P =0.0001) and submesothelial stromal clusters (SSCs) ( P =0.0008). SSCs ranged from subtle aggregates of spindle cells to nodules of whorled spindle cells with small vessels and extravasated red blood cells resembling stromal endometriosis. Immunohistochemical studies confirmed that ER and CD10-positive SSCs were present in a greater proportion of both nondiagnostic and diagnostic peritoneal biopsies and at a greater number of lesions per biopsy. The overall histologic detection rate of peritoneal biopsies for endometriosis was 62.0%, and inclusion of SSCs with or without foamy macrophages in the diagnostic criteria appreciably increased this rate to between 72.5% and 76.8%. We describe SSCs, which appear to be an early or less developed form of stromal endometriosis, and, when included in the diagnostic criteria, improve the histologic detection rate of endometriosis in peritoneal biopsies.